Breast Feeding and Weaning Practices in Thar Desert of Rajasthan, India - Singh, Madhu B; Lakshminarayan, J (Annals of Arid Zone, 2016)
Breast Feeding and Weaning Practices have a major effect on short term andlong term nutritional status of infants. An attempt was made to find out the patternof infant feeding practices in Thar Desert of Rajasthan so as to know the communityperceptions existing in this area. Data were collected from 434 young women belongingto rural house-holds of Thar Desert. Analysis revealed that exclusive breast feeding rate(